A New Approach for Privacy-Aware Smart Metering using the Concept of Software Defined Networking - Al-Haiqi, Ahmed; Alkahtani, Ammar Ahmed; Nordin, Farah Hani; Baharuddin, Mohd Zafri (International Journal of Engineering and Technology, 2018)
The direct and two-way communication between energy suppliers and high-frequency smart meters enables the suppliers to implement dynamic pricing and manage demand response. Fine-grained monitoring of energy consumption also helps consumers improve their energy profile. This granularity, however, may impose a threat on household privacy. Detailed profile of energy usage can be mapped into detailed profile of daily activities. Many proposals attempted to mitigate this problem and introduce privacy-preserving smart metering. The main approach is to process meter data before they are sent to the energy provider, through de-identification, aggregation or encryption. This processing can take place locally on the smart meter itself, or through a trusted third party. Such solutions suffer from increased smart meter complexity or increased infrastructure complexity, which may render them unacceptable. The idea described in this paper aims to avoid those drawbacks by proposing a new architecture to implement privacy-aware metering. The proposed approach employs the concept of software-defined networking (SDN) to manage smart-meter data in a separate control layer inside the home network. Leveraging the concept of SDN puts the control back in the hands of the consumers to manage their own privacy via SDN applications, and relieves the supplier from enduring extra complexities.